Voicing Out Women Issue Through #MencatatPengalamanPerempuan on Instagram - Rengganis Ranggita Ranggawuni; Kusuma, Rina Sari (Jogjakarta Communication Conference (JCC), 2025)
The rapid development of technology has changed the way humans access information and entertainment, offering the easier and quicker access to vast array of content, including discussions on gender equality or feminism. This research focuses on examining cyberfeminism within the context of Instagram, with a specific emphasis on the account of Kalis Mardiasih (@kalis.mardiasih). Cyberfeminism, is a theoretical framework, delves into the empowerment of women in the digital space, particularly on social media platform. Using a qualitative approach and employing the documentative content analysis method, this research analyzes the posts in the last 7 months on Kalis’s account that uses the hashtag #MencatatPengalamanPerempuan. By focusing on the content that associated with the mentioned hashtag, this research aims to explore how social media works as a platform for raising awareness about women’s issues. Through this method, the research seeks to shed light on the ways in which individuals like Kalis Mardiasih are leveraging Instagram as a tool for advocating for gender equality and amplifying women’s voices in the digital sphere. Contents that have been uploaded by Kalis Mardiasih in the decided period can be divided into three categories: (1) women in relationship with men (2) women in relationship and religious practice (3) women and their expression.